(untitled) (Journal of the College of Basic Education, 2023)
The research included study the adsorption of Clomid drug on the surface of activated carbon and zinc oxide. Many of parameters were studied which affect the adsorption process such as temperature, weight of adsorbent, equilibrium time, initial concentration and effect of pH. Activated carbon and zinc oxide were used as a model adsorbent in the experiments. We found that increased of temperature (30-50) °C followed by increased in adsorption capacity experiments were done at 30 °C and showed that the optimum weight of activated carbon was (0.15 g) while for zinc oxide was (0.1g), equilibrium time was (150 min) for the two adsorbents. The adsorption capacity of the two adsorbents increased with increasing initial concentration of drug, In addition, the experiments showed that the (3-7) pH was the best medium of the adsorption process.